Analisis Formulasi Dan Implementasi Kebijakan Penanganan Banjir Berkelanjutan Di Kota Bontang - Nelly Sampe; Muhammad Noor; Anwar Alaydrus (Bajang Institute, 2026)
Flooding is an urban problem that is not solely related to the capacity of drainage systems and rivers, but is also associated with spatial planning, changes in land use, institutional capacity, community participation, and policy consistency over the long term. Bontang City faces these challenges in the context of an industrial and coastal city characterized by local flooding, upstream flooding, and tidal flooding. This study aims to analyze the formulation and implementation of flood management policies in Bontang City from a sustainability perspective. The study employs a qualitative approach through document analysis of local regulations, development planning documents, technical planning documents, and relevant scientific literature. Policy formulation is analyzed based on the development of problem identification, objectives, instruments, actors, and policy orientation, while implementation is analyzed through policy standards and objectives, resources, interagency communication, characteristics of implementing organizations, implementers’ dispositions, and the social and political environment. The analysis shows that flood management policies in Bontang City have undergone institutional strengthening, from the preparation of academic papers and policy drafts to the enactment of Bontang City Regional Regulation Number 7 of 2024 on Flood Disaster Mitigation. Empirically, the flood-affected area in 2024 was recorded at 106.85 hectares, representing a 79.74% decrease compared with 2020. This decline indicates progress in policy implementation, particularly through river normalization, drainage development and rehabilitation, and the construction of flood control infrastructure. However, the policy orientation needs to be further strengthened so that it does not remain limited to a structural approach. Sustainable flood management requires integration of gray infrastructure, area conservation, risk-based spatial planning, long-term financing, cross-sectoral coordination, and community participation. This study emphasizes that the existence of regulations does not necessarily indicate the achievement of sustainable flood governance; policy effectiveness is largely determined by the government’s ability to integrate policy formulation with implementation capacity and collaborative governance